Investigating the Effect of Eight Weeks of Corrective Exercises and Ergonomic Recommendations on the Frequency of Recurrence of Back Pain Caused by Musculoskeletal Disorders in the Staff of Ardabil Sports and Youth Department - Aydin Ali khiavi; Mohsen Barghamadi; Mehrdad Moharramzadeh (Biyumikānīk-i varzishī)
Objective: Many annoying musculoskeletal pains and disorders are caused by the wrong habit and ‎ergonomics of the equipment in the workplace. Therefore, the aim of the present study was to ‎investigate the effect of eight weeks of corrective exercises, ergonomic recommendations on ‎the frequency of recurrent back pain due to musculoskeletal disorders in the staff of Ardabil ‎Youth and Sports Department‎. Methods: The present study is applied and quasi-experimental. The statistical sample included 60 ‎employees of the Sports and Youth Department of Ardabil province who participated in this ‎study voluntarily. They were randomly divided into three equal groups of corrective exercises, ‎ergonomic recommendations and control. The Nordic questionnaire was used to collect the ‎frequency of musculoskeletal disorders in the lumbar region and the frequency of recurrence of ‎pain as a pre-test and post-test. Will Coxon test was used to compare data between groups using ‎SPSS software version 26. Also, a significant level (p≤0.05) was considered for all tests. Excel ‎‎2010 software was used to draw the chart‎. Results: The findings of the present study showed that there is a statistically significant difference ‎between the group of corrective exercises and ergonomic recommendations and the frequency ‎of recurrence of pain due to musculoskeletal disorders (P = 0.022). There was also a significant ‎difference between the correctional exercise group and the control group in the frequency of ‎recurrence of pain due to musculoskeletal disorders‏ ‏‎(P = 0.001)‎. Conclusion: Providing corrective exercises significantly reduced the frequency of recurrence of pain due to musculoskeletal disorders in the lumbar region. Therefore, corrective exercises can be provided as useful and effective advice to reduce and eliminate the frequency of pain, especially to employees.